Pengembangan gim kuis edukasi suplemen buku ajar pengantar dasar IPA berbasis website - R Rohmani; Berta Apriza; Yasinta Mahendra (JINoP (Jurnal Inovasi Pembelajaran), 2021)
Technological developments in the digital era demands innovation in learning. Learning innovation is developed according to the needs and demands of solving problems in the field. This study aimed to develop a supplementary basic introductory science textbook in the form of a website-based quiz game that can be accessed using a smartphone. The textbook supplement quiz game was created with the aim of maximizing the use of smartphones owned by students and reducing the negative impacts of using smartphones in learning. The method in this study was Research and Development (R&D) method using a procedural model. The data collection instruments in this study were validation sheets, student response questionnaire sheets, and test questions. The test subjects in this study were 73 students of the elementary school teacher education program at the Muhammadiyah University of Kotabumi. The results of the quiz game feasibility test were 79.42% and were declared eligible because they were greater than 61%. The level of effectiveness of the quiz game is 90.47% and is declared effective because it is greater than 80%. Practical test of the practicality of using quiz games by 87.06% was declared practical because it was greater than 61%. The use of quiz games supplementing the basic introductory science textbooks can improve student learning outcomes and be able to reduce the negative impact of smartphone use and maximize the benefits of using smartphones in learning.